Evaluation of paradoxical vocal cord motion and differential diagnosis - YalçInkaya, Esin; Güler, İsmail and Kocatürk, Sinan (ENT Updates, 2014)
Objective: To evaluate the relationship between paradoxical vocal cord motion (PVCM) disease and the diseases such as asthma, laryngopharyngeal reflux and anxiety disorder that should be taken into consideration most frequently in differential diagnosis. Methods: The study included 100 patients (64 females and 36 males) who had applied to the polyclinics of pulmonary diseases, gastroenterology, psychiatry and ear nose throat due to respiratory symptoms. In asymptomatic period, it was planned to diagnose paradoxical vocal cord motion due to inspiratory adduction and posterior glottic fissure observed in videolaryngoscopic examination made after provocative maneuvers. Results: The mean age of the patients was 44.7±7.3 (female: 36.3±4.5, male: 52.3±3.2). 57% of the patients applied to pulmonary diseases, 24% to gastroenterology, 12% to psychiatry and 7% to ENT polyclinics. No paradoxical vocal cord motion was detected in 99 patients invideolaryngoscopic examination made after provocative maneuvers performed in asymptomatic period. Paradoxical vocal cord motion was detected in one patient who had attack during videolaryngoscopic examination. Conclusion: Although PVCM is a rarely seen disease, it leads to serious problems in non-diagnosed patients. In our study, we concluded that PVCM can be diagnosed during an attack rather than provocativemaneuvers performed during asymptomatic period.